Application Of The Principle Of Equality Before The Law To Law Enforcement For The Realization Of Justice In Society - Purwadi, Wira; Djafar, Mohamad Ali Akbar; Densi, Gilang Fatirah; Tumiwa, Anika Zaitun; Langkamane, Arum Salsabila Yieputri (JURNAL LEGALITAS, 2022)
The consequences of the state of the law following the constitution mandate require that the application of law enforcement should be carried out somewhat based on equality before the law. The purpose of this study is to analyze how the principle of equality before the law applies to law enforcement for the realization of justice in society and to analyze the factors that hinder the realization of justice in applying the principle of equality before the law to law enforcement. This research uses normative legal research methods or library research. The results showed that applying the principle of equality before the law in law enforcement has not achieved the justice felt by the community. In terms of legal substance, legal structure, and legal culture